Legal Protection on Notary Who Made a Suspect in His Duty - Ine Rizka Ariyani; Bruyi Rohman Warsito; Gunarto Gunarto (Jurnal Akta, 2018)
Provisions concerning Notary regulated in Act No. 2 of 2014 on the Amendment of Act No. 30 of 2004 concerning Notary (hereinafter referred UUJN).[1] In Article 16 paragraph (1) letter (e) states that a Notary UUJN must preserve the confidentiality of all information obtained for a deed in accordance with their oath of office. In facing legal issues, Notary need an organization that can accommodate the aspirations and the problems it faces, so precisely that the Indonesian Notary Association (INI) into an organization that has continuity in carrying out the supervision, guidance and legal protection for a notary.The research objective is to analyze the legal protection of a notary is used as a suspect in the running of their office, to analyze problems and solutions of legal protection against notaries who serve as a suspect in carrying out his duties.The method used in this research is juridical empirical method is a method of legal research that attempts to view the law in terms of real or can be said to see, examine how the workings of the legal community.The results of this study finally provides an answer that before a notary dragged to criminal law to the case of giving false testimony, the investigator must know what the principal case of the case. Due to lack of caution can make  Notary as a suspect. Notaries in carrying out its duties merely formal and only constantire wishes of the parties and then poured into deed. Because there is one of the aggrieved party in the matter and notary asked by investigators to show the deed and is of public interest and obtain permission from MKN, then Article 16 (1) f and Article 54 UUJN about keeping positions can be ruled out because there are interests higher should notary testified that noataris released from his oath of office according to the rules applicable legislation. MKN legal protection given to the Notary ie if it will initiate an investigation or calling to the Notary must ask permission first terelebih to MKN, must coordinate with the IT organization or the competent senior Notary.Keywords: Legal Protection; Suspect; Notary.